Analysis of Skill Improvement in Video and Photo Editing of High School Students: A Case Study of SMA 1 Sungai Raya Kepulauan - Alfian Abdul Jalid; Hengky Anra; Eva Faja Ripanti; Novi Safriadi; Anggi Perwitasari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2023)
Proficiency in video editing offers many advantages due to the market demand from various sectors such as pre-wedding, wedding events, religious ceremonies, office activities, schools, universities, and more. The need to document personal moments in the era of globalization is increasing. Although video editing is included in the high school curriculum, the reality is that not many high school graduates are proficient in video editing. Therefore, it is necessary to provide more intensive training to high school students so that they do not become unemployed after graduation. This research aims to evaluate the influence of training and mentoring on the improvement of video and photo editing skills among students of SMA 1 Sungai Raya Kepulauan. The study involves two groups: an experimental group that receives training and mentoring, and a control group that does not receive similar treatment. The results of this research are expected to provide a better understanding of the effectiveness of the training and mentoring program in enhancing multimedia skills among students of SMA 1 Sungai Raya Kepulauan.